DETERMINAN YANG MEMENGARUHI KEMISKINAN DI INDONESIA - Melki Eddy Rantung; Feliks Arfid Guampe; Olvit Olniwati Kayupa; Yulian Rinawaty Taaha (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2026)
This study aims to examine the influence of life expectancy, literacy rate, and per capita expenditure on poverty levels in Indonesia. The research applies a quantitative approach using multiple linear regression to analyze the relationships among variables. The study utilizes secondary time-series data covering the period from 2005 to 2022, consisting of 18 annual observations obtained from official publications of Statistics Indonesia (BPS). Prior to regression analysis, classical assumption testing was conducted, particularly the normality test. Hypothesis testing was carried out using the t-test to assess partial effects, the F-test to examine simultaneous effects, and the coefficient of determination (R²) to measure the explanatory power of the model. The findings reveal that life expectancy, literacy rate, and per capita expenditure jointly have a significant effect on poverty levels in Indonesia. Partially, per capita expenditure significantly contributes to reducing poverty, while life expectancy and literacy rate do not exhibit statistically significant effects during the observation period. The coefficient of determination indicates that a substantial proportion of the variation in poverty levels can be explained by the three independent variables included in the model. These results highlight the importance of improving economic welfare as a key element in poverty reduction efforts.